Meniti Cinta dari Jauh: Eksplorasi Komitmen dalam Pacaran Long Distance Relationship (LDR) - Irene Miracle Philian Goszal (Fakultas Psikologi Universitas Kristen Satya Wacana, 2024)
Long Distance Relationship (LDR) or long-distance dating is a common phenomenon occurring nowadays. In LDR dating, many dynamics and issues arise due to the limitations in physical contact, communication, and meeting. This research aims to explore in more depth how the picture of commitment is applied as a strategy by couples in long-distance relationships or LDRs. The method in this research uses a qualitative method by applying thematic analysis. The participants of this study involved four participants who are currently in a long-distance relationship (LDR). Data collection was carried out using interview techniques and observation. The research results show the dynamics of commitment in long-distance relationships: commitment in providing support, empathy and attention, as well as responsibility in the relationship.